2013
DOI: 10.1038/ncomms3878
|View full text |Cite
|
Sign up to set email alerts
|

Abstract rule neurons in the endbrain support intelligent behaviour in corvid songbirds

Abstract: Despite the lack of a layered neocortex and fundamental differences in endbrain organization in birds compared with mammals, intelligent species evolved from both vertebrate classes. Among birds, corvids show exceptional cognitive flexibility. Here we explore the neuronal foundation of corvid cognition by recording single-unit activity from an association area known as the nidopallium caudolaterale (NCL) while carrion crows make flexible rule-guided decisions, a hallmark of executive control functions. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
123
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 54 publications
6
123
1
Order By: Relevance
“…Tracing electrode tracks of an identically implanted crow used for a different study (25,26) confirmed that recording locations were within NCL. Cryostat sections were immunohistochemically stained for tyrosine-hydroxylase to identify dopaminergic cells, which characterize the NCL (25). Both crows used in this study are still alive and are participating in related experiments.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Tracing electrode tracks of an identically implanted crow used for a different study (25,26) confirmed that recording locations were within NCL. Cryostat sections were immunohistochemically stained for tyrosine-hydroxylase to identify dopaminergic cells, which characterize the NCL (25). Both crows used in this study are still alive and are participating in related experiments.…”
Section: Methodsmentioning
confidence: 94%
“…The birds' lineage diverged from mammals 300 Mya (19), at a time when the neocortex had not yet developed from the pallium of the endbrain. Instead, birds developed different pallial parts as dominant endbrain structures (20,21) based on convergent evolution, with the nidopallium caudolaterale (NCL) as a highlevel association area (22)(23)(24)(25)(26). Where and how numerosity is encoded in vertebrates lacking a neocortex is unknown.…”
mentioning
confidence: 99%
“…Birds can also be trained in the laboratory to distinguish stimuli based on the number of items [8,22,23]. Corvid songbirds are renowned for their flexible behaviour [24], making them ideal model organisms for the study of cognition [25,26] and high-level brain functions [27][28][29][30]. Ever since Koehler and his co-workers explored the numerical capabilities of birds [31], corvids have been known to show some level of quantity discrimination [32], and they use quantity rules to direct behaviour [33].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that single NCL neurons encode abstract behavioral rules, irrespective of the arbitrary, learned cues used to instruct the rule (4). Furthermore, pigeons with lesions of the NCL show deficits in a reversal learning task, indicating that the NCL is a crucial structure to flexibly adapt behavior based on feedback during learning (5).…”
mentioning
confidence: 99%